Endogenous galectin-3 controls experimental malaria in a species-specific manner - Toscano, Marta Alicia (2012)
Galectins are evolutionarily conserved glycan-binding proteins with pleiotropic roles in innate and adaptive immune responses. Galectin-3 has been implicated in several immunological processes as well as in pathogen recognition through specific binding to glycosylated receptors on the surface of host cells or microorganisms. In spite of considerable evidence supporting a role for galectin-3 in host–pathogen interactions, the relevance of this lectin in the regulation of the host defence mechanisms in vivo is poorly understood. In this study, we analysed the impact of galectin-3 deficiency during infection with three distinct species of rodent malaria parasites, Plasmodium yoelii 17XNL, Plasmodium berghei ANKA and Plasmodium chabaudi AS. We found that galectin-3 deficiency showed a marginal effect on the course of parasitaemia during P. chabaudi infection, but did not alter the course of parasitaemia during P. berghei infection. However, lack of galectin-3 significantly reduced P. yoelii parasitaemia. This reduced parasitaemia in Lgals3−/− mice was consistent with higher titres of anti-P. yoelii MSP119 IgG2b isotype antibodies when compared with their wild-type counterparts. Our results reflect the complexity and singularity of host–pathogen interactions, indicating a species-specific role of endogenous galectin-3 in the control of parasite infections and the modulation of antibody responses.